Sports Coaches’ Knowledge and Beliefs About the Provision, Reception, and Evaluation of Verbal Feedback - Mason, Robert J.; Farrow, Damian; Hattie, John A. C. (Frontiers in Psychology, 2020)
Abstract. Coach observation studies conducted since the 1970s have sought to determine the quantity and quality of verbal feedback provided by coaches to their athletes. Relatively few studies, however, have sought to determine the knowledge and beliefs of coaches that underpin this provision of feedback. The purpose of the current study was to identify the beliefs and knowledge that elite team sport coaches hold about providing, receiving and evaluating feedback in their training and competition environments. Semi-structured interviews conducted with 8 coaches were inductively analysed, revealing three broad themes: thinking and learning about feedback, providing feedback, and evaluating feedback. Findings revealed a detailed array of knowledge about feedback across a wide range of sub-topics. Coaches saw feedback as a tool to improve performance, build athlete confidence, help athletes to monitor progress, and as a tool to improve their own performance. Novel insights about evaluating an athlete’s reception of feedback, and tailoring feedback for individual athletes, were provided by coaches. The findings also highlight areas in which future coach education offerings can better support coaches to provide effective feedback.